JURIDICAL REVIEW ON PROCEDURES FOR PLOTTING AND SELLING OF LAND PLOTS BASED ON THE LAND LAW AND ITS IMPLEMENTING REGULATIONS - Mieke Anggraeni Dewi; Mig Irianto Legowo; Kuswarini Kuswarini (Jurnal Meta-Yuridis, 2023)
This study aims to find the legal arrangements, especially the Land Law and its Implementing Regulations which can guide the procedures for land plotting that occur in the community, regarding its procedure for buying and selling land rights in relation to the land plots. The research method used is the normative juridical research method. Legal arrangements and procedures for land plotting in Indonesia are regulated in a statutory regulation, namely the UUPA and PP No. 24 of 1997 Article 48 and Article 49 PP No. 24 of 1997 which regulates division and separation as a legal reference regarding the land division. The procedure for managing land plots can be done in 2 ways, namely land parcels through the Procedure for Separation of Self-titled Titles, and Land Plots Directly through the Sale and Purchase of Land Rights. The procedure for buying and selling land rights in relation to plotting is carried out through 4 stages as follows: stage 1, the seller of the land plot (land plotter) submits an application for registration of splitting of NIB (Land Plot Identification Number) which must be carried out before an official sale and purchase transaction is carried out, in the sense that there has been no payment to the land owner because the PPAT deed has not been made. Then, in Stage 2, all processes related to plotting, namely splitting and separating land parcels in the field, including measurements made at the time of application for NIB registration. Lastly, in Stage 3, after the NIB registration application process is complete, the Land Agency Office issues a map of the land parcels in which the NIB of the relevant land parcel is stated